Interventions in occupational health psychology. - Beehr, Terry A. (Journal of Occupational Health Psychology, 2019)
The set of studies in this issue focus on applied interventions in occupational health psychology (OHP), that is, interventions that are intended to treat employee health and well-being problems or prevent these problems from occurring in the first place. An issue regarding many past evaluations of the effectiveness of these treatments was the relatively weak research methods, especially in regard to obtaining comparable groups to study so that internal validity is enhanced. Many of the studies presented here used the classically recommended approach of random assignment to alleviate this potential problem. We can see that there are a variety of types of potential treatments in OHP, including interventions focusing on changing the employee, other people in the employee's workplace (supervisors or coworkers), the employee's job characteristics, or the organization's climate. Although the ultimate criterion variables in OHP are indicators of employee wellness, some studies focused on improving what might theoretically be mediating variables between the interventions and employees' actual health or well-being. These outcomes include reductions of work-nonwork conflict and stigma of mental illness potentially present in the organization, its supervisors, or employees' coworkers. We note that there are probably moderators of the effectiveness of the interventions, so that a treatment may work better in some people, some situations, and some times than others. Finally, it is interesting to note that the interventions and their studies may be geographically concentrated rather than distributed equally around the globe. (PsycINFO Database Record (c) 2019 APA, all rights reserved).